The Influence of Letter Card Media on Learning Outcomes of Class 1 Students in Learning Theme 1 Myself Subtema 2 Me and New Friends at SDN 091277 Pematang Siantar - Jelita Sirait; Lisbet Novianti Sihombing; Sukardo Sitohang (International Journal of Integrated Science and Technology, 2023)
This research aims to determine the effect of letter card media on the learning outcomes of grade 1 students in learning theme 1 myself, sub-theme 2, me and my new friends at SDN 091277 Siantar Estate. The method in this research is a quantitative experimental type method whose research design is pre-experimental type one group pretest-posttest. The population and sample used is saturated sampling with a sample of 22 people with two research variables: the dependent variable (x) in the form of learning outcomes, and the independent variable (y) in the form of letter card media. The data collection technique is the test technique. The test results using the T-test with the help of the SPSS version 21 program, based on the calculation results obtained tcount = 22,906 with a significance level (2-tailed) 0.000, significant probability < 0.005, tcount > ttable = 22.906 > 2.074, so H0 is rejected and Ha is accepted. This explanation shows that there is an influence of letter card media on the learning outcomes of class I students in the Sub-theme Me and New Friends at SDN 091277 Siantar Estate.